A critique of Thad Metz's African theory of moral status. Issue 2 (2nd June 2017) - Molefe, Motsamai
Abstract : Thad Metz defends what he considers to be a novel theory of moral status, i.e. an account about what beings are owed direct duties in virtue of their moral significance. Metz claims that his account is African, it is plausible and that it is worth taking seriously like other competing accounts in the Western philosophical tradition. In this article, I give four reasons why we should doubt, if not reject, these claims of plausibility. Firstly, I show how a theory that accounts for moral status by relying solely on some facet of human nature ultimately fails to grant intrinsic value to non-human components, and as such it will always prefer human interests over those of nonhuman components, and further it won't have a moral-theoretical basis to assign intrinsic value to non-human components. Secondly, I hope to demonstrate that this theory will not be able to account for the moral status of Martians and in turn show that it does not secure the standing of animals from such beings. I also argue that his account does not give credible evidence for the intuition that severely injured human persons have greater moral status than animals with similar internal properties. Finally, I briefly indicate that this theory does not have the corpus to explain our duties to people who have died, or at least, their bodies.